Which Individuals with Positive Family History of Gastric Can-cer Urgently Need Intensive Screening and Eradication of Heli-cobacter Pylori? A Systematic Review and Meta-Analysis - Gui He; Xuanke Ji; Yali Yan; Kunyan Wang; Chunhua Song; Peng Wang; Hua Ye; Liping Dai; Jianying Zhang; Kaijuan Wang (Tehran University of Medical Sciences, 2021)
Background: Family history may inform individuals that they are at risk of gastric cancer (GC). However, it is too extensive to conduct intensive screening strategies for all individuals with family history of GC instead of average-risk screening. To establish more precise prevention strategies, accurate risk estimates are necessary for individuals with family history of GC. Methods: We searched PubMed, EMBASE and Cochrane for all relevant studies from their inception to May 21, 2020, for cohort and case-control studies investigating the association between family history of GC and its risk. Relative risk (RR) and 95% confidence interval (CI) were pooled from studies using random-effects or fixed effects. Results: The RR of GC was 2.08 (95% CI=1.86-2.34) in individuals with family history of GC according to twenty-nine case-control studies and 1.83 (95%CI=1.67-2.01) from six cohort studies. The increased risk was higher in individuals with sibling history of GC than those with parental history of GC (RR=3.18, 95% CI=2.12-4.79 vs. RR=1.66, 95% CI=1.46-1.89, P=0.021). For individuals with 2 or more first-degree relatives (FDRs) with GC, the RR was 2.81(95% CI=1.89-3.99). Subjects with both family history and Helicobacter pylori (H. pylori) infection confer a higher risk of GC (RR = 4.03, 95%CI=2.46-6.59). Conclusion: The RR of GC among FDRs is lower than in previous studies. However, the risk of GC is markedly increased in individuals having a sibling with GC, more than 2 FDRs with GC. Intensified screening and eradication therapy for H. pylori could be considered for these individuals.